A heterotopology of the academy: mapping assemblages as possibilised heterotopias. Issue 4 (21st April 2017) - Charteris, Jennifer; Jones, Marguerite; Nye, Adele; Reyes, Vicente
Abstract: Heterotopias are counter-sites of enacted utopias through which reality is simultaneously represented, contested and inverted. They are physical or mental spaces where, although norms of behaviours are suspended, there are connections with a plethora of other spaces. This article constructs a collective biography as a heterotopology of the academy. Academic subjectivities are produced and often constrained within powerful Higher Education discourses. Constructing an affective assemblage of becomings as a heterotopology, the authors deploy poststructural philosophy to re-story academic life experiences and conceptualise agency in the academy. Taking licence with the notion of academicity and heterotopia, the article describes how spaces in the measured university can be deterritorialised through generative lines of flight. An affective assemblage is presented that ruptures the discursive orientation of category boundary work where academics are constituted as 'productive metric-minded knowledge workers'. The collective biography research approach facilitates a mapping of affective cartographies as a heterotopology and a critique of the discursive production of selves. The subjectivations of identity politics in matricised assemblages may be, even if momentarily, evaded, refused and agentically resisted.